2021
DOI: 10.3390/fermentation7040229
|View full text |Cite
|
Sign up to set email alerts
|

Net Energy Analysis and Techno-Economic Assessment of Co-Production of Bioethanol and Biogas from Cellulosic Biomass

Teeraya Jarunglumlert,
Chattip Prommuak

Abstract: Co-production is a process based on the biorefinery concept that maximizes the benefit of biomass by reusing residue from the production of one product to produce others. In this regard, biogas is one of the most researched second products for the production of ethanol from cellulosic biomass. However, operating this scheme requires additional investment in biogas processing equipment. This review compiles data from research studies on the co-production of bioethanol and biogas from lignocellulosic biomass to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…8, schemes 1 and 2, which allow the production of bioethanol prior to biogas, generated an average total bioenergy output of 9.8 and 7.8 MJ/t biomass, respectively. In contrast, scheme 3, where AD comes before fermentation, generated a relatively lower energy output of 6.4 MJ/T 111 . The observed variation can be tied to the differences in process configuration, including feedstock types, pre‐treatment techniques, and process conditions.…”
Section: Techno‐economic Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…8, schemes 1 and 2, which allow the production of bioethanol prior to biogas, generated an average total bioenergy output of 9.8 and 7.8 MJ/t biomass, respectively. In contrast, scheme 3, where AD comes before fermentation, generated a relatively lower energy output of 6.4 MJ/T 111 . The observed variation can be tied to the differences in process configuration, including feedstock types, pre‐treatment techniques, and process conditions.…”
Section: Techno‐economic Analysismentioning
confidence: 98%
“…The overall gross bioenergy output from the co‐production process can be higher. For example, in the review of Jarunglumlert et al ., the average biofuel output from the co‐production process was estimated at 8 MJ/T dry biomass, which is equivalent to 250 L gasoline, indicating a 142% increase than producing bioethanol alone and 70% increase than producing biogas alone 111 . From Fig.…”
Section: Techno‐economic Analysismentioning
confidence: 98%
“…The former system uses cellulolytic enzyme cocktails for breaking down the biomass into sugars, which can then be further processed into fuels (e.g., ethanol) by microorganisms such as brewer's yeast ( Saccharomyces cerevisiae ) (Chundawat et al, 2011). In contrast, AD systems employ undefined mixed microbial cultures that are responsible for both disintegrating and converting the biomass, often into methane‐rich biogas (Jarunglumlert & Prommuak, 2021; Monlau et al, 2013). A major impediment to biological conversion of lignocellulose biomass is its inherent resistance to deconstruction, a property commonly referred as biomass recalcitrance (see Section 2).…”
Section: Conversion Of Salix Biomass Into Liquid and Gaseous Transpor...mentioning
confidence: 99%
“…Since the late 1980s and until today, willow biomass has been used almost exclusively commercially as biofuel in the form of wood chips for direct combustion in heat and power plants (Kuzovkina et al, 2008). However, there is also a growing interest of using this biomass as raw material for conversion into other biofuels such as biogas and bioethanol (Jarunglumlert & Prommuak, 2021; Phitsuwan et al, 2013), a development that likely requires genetic improvements of additional breeding targets compared to using willow biomass solely for direct combustion. To date, Salix breeding programs have produced varieties for the European as well as the international market (Karp et al, 2011; Smart & Cameron, 2008) and varieties with increased yield and resistance toward different pests, especially rust fungi ( Melampsora epitea ) are now available (Åhman et al, 1994; Karp et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the co-production process in this context refers to the production of other fuels or valuable substances as a by-product of ethanol production, which can be sold to increase revenue or used as fuel to reduce energy costs in ethanol production. As a result, the economic competitiveness of second-generation bioethanol production is enhanced [21]. In this regard, previous research has demonstrated the production of bioethanol coupled with biogas from red oak [22], sugarcane bagasse [23], wheat straw [24], corn stover [25], spruce wood [26], and switchgrass [27].…”
Section: Introductionmentioning
confidence: 99%